The Regaining Territory of the Ojibwa Tribe in Louise Erdrich’s The Birchbark House Book Series - Ramadhina Ulfa Nuristama (Universitas Gadjah Mada, 2017)
Native American people have been experienced in confronting the white people. One of their experiences in confronting the white people is written in the Louise Erdrich’s literary works, an Ojibwa author. Native American authors have different point of view in telling about Native Americans because they and their ancestors have bitter experiences in dealing with the white people, especially the Ojibwa tribe’s experiences living in the America where other Native American tribes cannot survive their tribes. This research focuses on the struggles of the Ojibwa people in getting their territory and the reasons why the Ojibwa people try so hard in keeping their territory. This research uses historical approach in its analysis. The method used is qualitative method related to literature study by using the five books of The Birchbark House book series as the primary data of this research. There are several conclusions based on the analysis of the data. The Ojibwa people are able to maintain their tribal presence in America against the white people. They can defend their tribe by using their intelligence, courage, and self-confidence. As for the reasons they prefer to choose their own way in getting territory because of several factors such as beliefs, relatives, and natural conditions of the land. Keywords: Historical Approach, Indian Territory, Native American, Ojibwa.